Hepatic artery pseudoaneurysm–the Mayo Clinic experience and literature review - Tatjana Gavrancic; Muhammad Waqas Tahir; Marko Gorasevic; Igor Dumic; Libardo Rueda Prada; Melissa Cortes; Patricia Chipi; Zlatko Devcic; Charles Ritchie; Aleksandra Murawska Baptista (Frontiers in Medicine)
IntroductionHepatic artery pseudoaneurysm (HAP) is a rare and potentially life-threatening condition associated with high mortality. This study aims to review the etiology, clinical manifestations, management, and outcomes of patients diagnosed and treated for HAP at the Mayo Clinic.MethodologyThis study was a retrospective chart review of medical records for patients diagnosed and treated for hepatic artery pseudoaneurysm (HAP) at the Mayo Clinic (Florida, Minnesota, and Arizona) between September 1, 1998, and June 30, 2022. A total of 27 patients with HAP were identified, and their demographics, presenting symptoms, location of HAP, etiology, associated liver pathology, type of intervention, and outcomes were analyzed.ResultsThe majority of patients with hepatic artery pseudoaneurysm (HAP) were male (63%), with a median age of 57 years (range: 25–87 years). HAP was predominantly intrahepatic (85.2%) and most commonly located on the right hepatic artery (RHA) (70.4%). In 89.9% of cases, the condition was attributable to hepatobiliary procedures or trauma, while only 10.1% occurred spontaneously. Presenting symptoms at the time of HAP diagnosis varied, including gastrointestinal (GI) bleeding (29.6%), abdominal pain (14.81%), non-GI bleeding (11.1%), traumatic bodily injury (11.1%), and other symptoms (14.81%). Asymptomatic or incidental findings of HAP were observed in 18% of cases. Malignancy was identified in 52% of patients, and 26% were liver transplant recipients. Statistical analysis revealed that factors such as prior knowledge of HAP (p = 0.381), HAP rupture (p = 0.382), anticoagulation therapy (p = 0.856), hemorrhagic shock (p = 0.25), liver cirrhosis (p = 0.143), gastrointestinal bleeding (p = 0.879), hepatobiliary abscess (p = 0.079), liver transplantation (p = 0.738), spontaneous HAP (p = 0.381), and malignancy (p = 0.163) were not significantly associated with increased mortality. In contrast, the need for transfusions (p = 0.021), tumor invasion (p = 0.023), portal vein thrombosis (PVT) (p = 0.02), and liver necrosis (p = 0.02) were significantly associated with higher mortality. The overall infection rate was 3%, while the mortality rate was 18.5%.DiscussionHepatic artery pseudoaneurysm (HAP) is a rare but serious condition often associated with hepatobiliary procedures, trauma, or liver transplants, though it can also occur spontaneously. While HAP is commonly detected incidentally, its diagnosis is frequently linked to complications such as rupture and gastrointestinal bleeding. However, our study suggests that these complications do not necessarily increase mortality. Key factors associated with higher mortality include the need for blood transfusions, tumor invasion, portal vein thrombosis, and liver necrosis at the time of diagnosis. The overall infection rate was low, but the mortality rate was 18.5%, highlighting the importance of early detection and management.